Carbon deposition by Russian forests on the example of taiga and forest-steppe zones - Usoltsev, Vladimir Andreevich; Zukow, Walery; Tsepordey, Ivan Stepanovich (Ecological Questions, 2021)
Due to the global warming of the climate, the assessment of the carbon cycle in forest ecosystems has become particularly important. One method for determining deposited carbon is based on the use of biomass expansion factors (BEF) and State Forest Inventory (SFI) data. By combining BEF models with SFI data in two ecoregions of Russia – taiga and forest-steppe - it was found that over a 20-25-year period, accumulating the carbon deposition in the taiga zone is significantly less (5%) compared to the forest-steppe zone (39%). Comparable results were obtained by the same method in different ecoregions of the planet (from 8% in 5 years in China to 68% in 50 years in Japan). A comparison of the results obtained by the proposed method and the IIASA method showed a minimal discrepancy (3 %), which gives reason to consider the above estimates of carbon deposition close to reality. However, uncertainties remain related to the quality of the SFI data and the carbon deposition in the soi